If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12.50+3/9=x
We move all terms to the left:
12.50+3/9-(x)=0
We add all the numbers together, and all the variables
-1x+12.5+3/9=0
We multiply all the terms by the denominator
-1x*9+3+(12.5)*9=0
We add all the numbers together, and all the variables
-1x*9+115.5=0
Wy multiply elements
-9x+115.5=0
We move all terms containing x to the left, all other terms to the right
-9x=-115.5
x=-115.5/-9
x=12+5/6
| 2x+(6x-7)=(103-x) | | 33=99-x | | 2(1/2x-6)=11 | | (x)=3x^2+1 | | 100=12x+13Y | | F(-5)=x^2-2x+7 | | (9x+16)(19x+3)(6x+15)=180 | | 3r=-42 | | 12.50+5/9=x | | 12=15n=33 | | 1x+1.2x-5.4=−10 | | 2({1}{2}x-6)=11 | | -28=x+4 | | 3(x-5)^2=363 | | 2/3x-8=x-17 | | 27=12x+6x+1+2 | | (2x+3)=(9x-25) | | 12(f+5)=138 | | 3(x–5)=2x–3 | | 4g-36=-12 | | 27=12x+1+2 | | -18=-9c | | 3+5x=(4x+7)=4(7x+3)-3 | | 9x44+6x+3=77 | | 1.2*8.5=1.7x | | -3x+4=5x+7 | | 2*x1x=49 | | -4.5+4.5=+y3 | | n=17.53-n | | 11+1x+22=67x+33 | | x/10=3.5/4 | | 4(x+2)=-(x-33) |